Hypothalamic Vitamin D Improves Glucose Homeostasis and Reduces Weight - Sisley, Stephanie R.; Arble, Deanna M.; Chambers, Adam P.; Gutierrez-Aguilar, Ruth; He, Yanlin; Xu, Yong; Gardner, David; Moore, David D.; Seeley, Randy J.; Sandoval, Darleen A. (Diabetes (New York, N.Y.), 2016)
Despite clear associations between vitamin D deficiency and obesity and/or type 2 diabetes, a causal relationship is not established. Vitamin D receptors (VDRs) are found within multiple tissues, including the brain. Given the importance of the brain in controlling both glucose levels and body weight, we hypothesized that activation of central VDR links vitamin D to the regulation of glucose and energy homeostasis. Indeed, we found that small doses of active vitamin D, 1α,25-dihydroxyvitamin D3 (1,25D3) (calcitriol), into the third ventricle of the brain improved glucose tolerance and markedly increased hepatic insulin sensitivity, an effect that is dependent upon VDR within the paraventricular nucleus of the hypothalamus. In addition, chronic central administration of 1,25D3 dramatically decreased body weight by lowering food intake in obese rodents. Our data indicate that 1,25D3-mediated changes in food intake occur through action within the arcuate nucleus. We found that VDR colocalized with and activated key appetite-regulating neurons in the arcuate, namely proopiomelanocortin neurons. Together, these findings define a novel pathway for vitamin D regulation of metabolism with unique and divergent roles for central nervous system VDR signaling. Specifically, our data suggest that vitamin D regulates glucose homeostasis via the paraventricular nuclei and energy homeostasis via the arcuate nuclei.